IVsight as an Infusion Monitor for Patients Receiving Intravenous Therapy: An Exploratory, Unblinded, Single-Center Trial - Carlos Mejia-Chew, MD; Brett Heuring, PharmD; Jeffrey Salmons, RN; Lori Weilmuenster, PharmD; Joe Beggs, BEng; Glen Kleinschmidt, BEng; Jake Eshelman, BEng; Sai Dodda, PharmD (Elsevier, 2024)
ABSTRACT: Background: Intravenous (IV) infusion therapy is commonly used in health care settings. However, IV therapy at home can be challenging because it relies on the patient's ability to manage multiple medications correctly, which may lead to decreased treatment adherence. Objective: We aimed to assess the usability and accuracy of the IVsight monitor in capturing IV infusion data compared to manual recording. Methods: A prospective, single-center, usability study involving patients receiving IV infusion therapy at one of the BJC's Home Infusion suites was conducted to evaluate the accuracy, performance, and acceptability of the device IVsight as a monitor for IV infusions. Results: Of the 15 participants, the median (IQR) age was 46 years (36-55), 8 (53%) were female, and 13 (87%) were non-Hispanic white. Each participant received a median (IQR) of 4 (4-5) infusions during the study, and 68 infusions were observed overall. The intraclass correlation coefficient between the IVsight measurement and manual recording of infusion duration in seconds was excellent (ICC 0.97, 95% confidence interval 0.96-0.98). The Bland-Altman plot visually showed an acceptable limit of agreement for the 2 measurements, and the linear regression analysis revealed no significant proportional bias between the 2 methods for measuring the IV infusion time. None of the participants thought that IVsight was difficult to hold, use, clean, or store. Only one participant was concerned that the device could interfere with the IV infusion, and all participants felt comfortable with the device transmitting data to their health care providers. Conclusions: The IVsight infusion monitoring device showed near-perfect agreement on the recorded IV infusion duration compared with manual recording, and good acceptability among the study participants.